Perception and Preference of the Campus Landscape Aesthetic Quality Faculty of Agriculture Udayana University - Jimbaran Bali - RIZKY ADITYA RIFAI; I NENGAH ARTHA; IDA AYU MAYUN (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana)
ABSTRACT Perception and Preference of the Campus Landscape Aesthetic Quality Faculty of Agriculture Udayana University - Jimbaran Bali Generally the Faculty of Agriculture Udayana University Jimbaran Bali landscape has not been organized properly, except around the administration building. Unorganized landscape can be seen from visual quality or the aesthetic. This research aims to know students’ perceptions and preferences about the college landscape aesthetic, especially between organized and unorganized landscape areas. This research used Semantic Differentials measurement methods. The result shows that students’ perceptions of the campus landscape aesthetic based on form and color-scoring criteria are monoton, informal, linear, bright, cold, and secondary color. Keywords: aesthetic, campus landscape, perceptions, preferences, Semantic Differentials